HUBUNGAN ANTARA KONSEP DIRI DAN KECERDASAN EMOSIONAL TERHADAP EMPATI SISWA - Tahsyah Nabilah Putri Agradewi; Zaki Nur Fahmawati (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This study aims to determine the relationship between self-concept and emotional intelligence on empathy. This research method uses a correlational quantitative approach with analysis techniques using multiple linear regression with the help of SPSS. Collecting data using a questionnaire with a population of 345 respondents. Sampling using random sampling. The results of this study indicate a relationship between empathy and self-concept of 0.126 and a relationship between empathy and emotional intelligence of 0.366. So that there is a relationship between the independent variables (self-concept and emotional intelligence) to the dependent variable (empathy) that is equal to 32.1% in a positive and significant way. Based on the coefficient table, it shows that self-concept has a significant influence on empathy. This can be seen from Sig < 0.05, namely 0.008 < 0.05, which means H0 is rejected. Meanwhile, in the Sig column. shows that emotional intelligence also has a significant influence on empathy, this can be seen from the value of Sig < 0.05, namely .000 < 0.05, which means H0 is rejected.